How capitalism abolishes itself in the digital era in favour of robo-economic systems: socio-economic implications of decentralized autonomous self-owned businesses. Issue 1 (1st November 2019) - Hoffmann, Christian Hugo; Dahlinger, André
Abstract : Purpose: The purpose of this paper is to explore socio-economic implications of decentralized autonomous self-owned businesses. Design/methodology/approach: The authors take the approach of a case study analysis. Findings: Unlike dark scenarios according to which almost half of our jobs are at risk in the wake of new emerging technologies such as AI and Blockchain (Frey and Osborne, 2013), the authors envision a world of decentralized autonomous self-owned businesses, using the example of the taxi market. The authors, first, outline their characteristics and how they work. Second, they elaborate on the socio-economic implications of markets where this novel kind of business enters. Third and most important, the authors argue that so-called robo-economic systems would be tantamount to a post-capitalistic society that is enforced by applying capitalistic principles. Research limitations/implications: The presented scenario of this paper is very futuristic and furthermore reduces a complex system quite drastically to be able to focus on the two implications of interest. Therefore, we are confronted with the necessity to take assumptions on socio-technical feasibilities and individual preferences. Most of these assumptions can be challenged (see Section 6.3). Social implications: The scenario presented by the authors stands in contrast to the fear that increased automation inherently leads to increased inequality. There is a general debate going on whether automation and digitalization will lead to a massive loss of employment, because machines will replace humans in many fields of work. Frey and Osborne (2013) estimate that nearly every second job is at risk to disappear in the coming decades because of computerization. Hence, many people fear to be left behind because of this development and inequality will increase tremendously as only those who own the machines will benefit directly from the profit share. In the scenario, however, the profits are mostly distributed among the consumers via reduced prices. Originality/value: The proposed scenario seems to reconcile socialism (less private property) with liberalism (a radicalization of markets) and shows an effective way to tackle market power, the problem that certain persons and firms would benefit almost exclusively from the increased profit margins promised by automation.